Species of Gyrodactylus von Nordmann, 1832 (Platyhelminthes: Monogenea) from cichlids from Zambezi and Limpopo river basins in Zimbabwe and South Africa: evidence for unexplored species richness - Zahradníčková, Petra; Barson, Maxwell; Luus-Powell, Wilmien J; Přikrylová, Iva (Systematic parasitology, 2016)
New findings on Gyrodactylus spp. parasitising African cichlids in southern Africa are presented, comprising data from Zimbabwe and South Africa. Morphometry of opisthaptoral hard parts in combination with nuclear ribosomal DNA sequences confirmed the presence of six species of Gyrodactylus von Nordmann, 1832. Three new species are described from fishes in Zimbabwe: Gyrodactylus chitandiri n. sp. from the gill arches of Coptodon rendalli (Boulenger) and Pseudocrenilabrus philander (Weber); Gyrodactylus occupatus n. sp. from the fins of Oreochromis niloticus (L.), Pharyngochromis acuticeps (Steindachner) and P. philander; and Gyrodactylus parisellei n. sp. from the fins of O. niloticus, P. philander and Tilapia sp. Gyrodactylus nyanzae Paperna, 1973 was also identified from the gills of O. niloticus and C. rendalli collected from two localities in Zimbabwe; these findings represent new host and locality records for this parasite. Gyrodactylus sturmbaueri Vanhove, Snoeks, Volckaert & Huyse, 2011 was identified from P. philander collected in South Africa and Zimbabwe thereby providing new host and locality records for this parasite. Finally, Gyrodactylus yacatli García-Vásquez, Hansen, Christison, Bron & Shinn, 2011 was collected from the fins of O. niloticus and P. philander studied in Zimbabwe; this represents the first record of this species from the continent of Africa. Notably, this study improves upon the knowledge of Gyrodactylus spp. parasitising cichlids from these southern African regions. All species studied were recorded from at least two different cichlid host species indicating trend for a wide range of Gyrodactylus hosts in Africa. Accordingly, this supports the idea of intensive host switching in the course of their evolution.
Keywords: Animals; Trematoda; biodiverzita; ribozomální DNA; Gills; DNA, Ribosomal; cichlidy; South Africa; druhová specificita; Rivers; Species Specificity; žábry; DNA, Helminth; Host Specificity; Phylogeny; Jihoafrická republika; Cichlids; Zimbabwe; DNA helmintů; ploutve zvířat; Animal Fins; řeky; Biodiversity; zvířata; fylogeneze; hostitelská specificita